2015
DOI: 10.1007/s11250-015-0905-5
|View full text |Cite
|
Sign up to set email alerts
|

Pathology and diagnosis of Mycobacterium bovis in naturally infected dromedary camels (Camelus dromedarius) in India

Abstract: The present study investigated the pathological features of tuberculosis (TB) caused by Mycobacterium bovis and its diagnosis in naturally infected dromedary camels from an organized farm in India. During the period of the 5-year study, a total of 18 (19.56 %) camels out of 92 examined showed gross lesions compatible with TB at post-mortem. The clinical signs and pathological lesions in these camels were studied, and the efficacy of different diagnostic tests was also assessed. On the basis of occurrence and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In our case, Animal 1 underwent behavioural changes and its body condition deteriorated owing to its progressive loss of appetite and weight loss, and was, in the final phase, intolerant to exercise. The type and distribution of the TB lesions observed in the infected animal studied herein were similar to those described in previous studies on M. bovis infected camels [9,10,13,22], suggesting that M. caprae caused a clinically and histologically indistinguishable infection. Nevertheless, the aforementioned authors noted three different gross patterns related to the distribution and incidence of TB lesions in dromedary camels: pulmonary, abdominal and disseminated forms.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our case, Animal 1 underwent behavioural changes and its body condition deteriorated owing to its progressive loss of appetite and weight loss, and was, in the final phase, intolerant to exercise. The type and distribution of the TB lesions observed in the infected animal studied herein were similar to those described in previous studies on M. bovis infected camels [9,10,13,22], suggesting that M. caprae caused a clinically and histologically indistinguishable infection. Nevertheless, the aforementioned authors noted three different gross patterns related to the distribution and incidence of TB lesions in dromedary camels: pulmonary, abdominal and disseminated forms.…”
Section: Discussionsupporting
confidence: 86%
“…The diagnosis of TB in OWC is based on various antemortem (intradermal tuberculin test, serology) and postmortem (pathology and bacteriological culture) techniques. However, the accurate ante-mortem diagnosis of TB is generally difficult, and few studies reporting the performance of TB diagnostic tests using different interpretation criteria in live OWC are available [4,13]. The use of the comparative intradermal tuberculin (CIT) test rather than a single intradermal tuberculin (SIT) test is usually preferred as a first option for diagnosis owing to the potential interference caused by environmental mycobacteria or Corynebacterium pseudotuberculosis infections [8,14].…”
Section: Introductionmentioning
confidence: 99%
“…Higher prevalence of camel tuberculosis (17%) has been reported in Northern Nigeria (Kudi et al, 2012), 33.5% in Zamfara (Ahmad et al, 2019) and 16.6% in Maiduguri (Abubakar et al, 2012. In Ethiopia, Zerom et al (2013) reported 12.3%, while in India Narnaware et al (2015) reported 19.5%. Our study also incriminated more camel cows with tuberculous lesions when compared to their male counterparts.…”
Section: Discussionmentioning
confidence: 98%
“…[21], who reported a prevalence rate of 8.3%, Narnaware et al . [22], who reported 19.56%, Jibril et al . [23], who reported 9.82%, and Ahmad et al .…”
Section: Discussionmentioning
confidence: 99%